Causes of Student Absenteeism: A Qualitative Investigation of Students’ Perception - Ghimire, Balkrishna Sharma (A Peer Reviewed Journal on Social Sciences, 2024)
This article explores the underlying causes of university students’ absenteeism, utilizing a qualitative approach to examine absentees’ perceptions. Absenteeism, defined as the intentional absence from classes, stems from various personal, financial, and institutional factors. The study identifies key contributors such as financial difficulties, transportation issues, disengaging curriculum, and ineffective teaching methods. Additionally, psychological challenges and logistical barriers like transportation and health issues are significant factors. The impact of absenteeism is far-reaching, affecting students’ academic performance, critical thinking skills, and social integration, potentially leading to higher dropout rates. By examining student perspectives, the study aims to uncover root causes and offer targeted recommendations to improve attendance. These include financial support, engaging curricula, improved teaching strategies, and institutional support services to address emotional and logistical barriers. This holistic approach seeks to create a more supportive academic environment, promoting student success and reducing absenteeism.